Argo - Affleck, Ben; Cranston, Bryan; Arkin, Alan; Goodman, John; Warner Bros. Pictures (United States : Warner Bros. Entertainment Inc., 2012)
As Iranian Revolution takes over the U.S. Embassy in Tehran, six Americans escape. Now only one man can get them out from behind enemy lines. Tony Mendez is a brilliant CIA agent who specializes in impossible escapes, but his new plan sight, where the slightest slipup could end in instant death.
Based on a selection from'The master of disguise' by Antonio J. Mendez and the Wired Magazine article'The great escape' by Joshuah Bearman.
Special feature: Rescued from Tehran: We were there ; President Jimmy Carter, Tony Mendez and the actual houseguests recount the real-life harrowing experiences they endured.
Based on the declassified true story.
Director of photography, Rodrigo Prieto ; production designer, Sharon Seymour ; editor, William Goldenberg ; costume designer, Jacqueline West ; music composed and conducted by Alexandre Desplat.
Ben Affleck, Bryan Cranston, Alan Arkin, John Goodman.
LPF: 18
Keywords: Mendez, Antonio J. -- Drama; United States -- Central Intelligence Agency -- Drama; Iran Hostage Crisis, 1979-1981 -- Drama; Americans -- Iran -- Drama